Extending Policy Implementation Theory for Natech Risk Governance: The KIKA-717 Model for Earthquake and Tsunami Mitigation in an Industrial Coastal City - Akhmad Taufan Maulana; Andriansyah Andriansyah; Nani Nurani Muksin; Evi Satispi; Azhari Aziz Samudra (Al-Makki Publisher, 2026)
Natural technological (natech) risks pose complex governance challenges in industrial coastal cities exposed to earthquakes and tsunamis. While policy implementation theories such as Edwards III remains influential, their explanatory power is limited when applied to multi-hazard, multi-actor, and technology-intensive disaster contexts. This study examines the implementation of Cilegon City Regulation No. 7/2017 on disaster management in Cilegon, Indonesia, a highly industrialized coastal city facing significant earthquake and tsunami risk. Using a qualitative case study approach involving in-depth interviews, document analysis, and field observation, this research identifies structural, institutional, and governance gaps that constrain effective mitigation. The findings demonstrate that deficiencies in communication, fragmented resource management, limited public participation, weak public trust, and rigid bureaucratic structures undermine policy effectiveness. To address these limitations, this study proposes the KIKA-717 model, an extended policy implementation framework integrating communication enhancement, integrated resource management, trust-based disposition, adaptive bureaucratic structure, public participation and partnership, information technology integration, and policy adaptability and learning. The model offers a transferable analytical and practical framework for strengthening disaster mitigation governance in industrial coastal cities facing natech risks.